UPAYA PENANGANAN TINDAK PIDANA PENIPUAN ONLINE OLEH SATRESKRIM POLRES CIAMIS - adji, Adji Rizky ananda (Advances in Police Science Research Journal, 2020)
ABSTRACT ONLINE FRAUD HANDLING EFFORTS BY SATRESKIM POLRES CIAMIS ADJIE RIZKY ANANDA, 16.071 adjie.rizky262@gmail.com Motivated by a drastically incrase in online fraud cases without a balanced of good settlement. Indonesia is facing the digital era, where technology and information has started taking part from conventional method and giving new eases in daily life. Even some crimes always look for a way to grow. Indonesian National Police has the duty to enforce the law, maintain security and create order in society. In this case, Unit 2 Tipiter Satreskim Polres Ciamis holds the mandate to handle cyber crimes. Observant uses qualitative approaches with observation method and semi-structured interview to obtain in-depth information. Observations were made in Kabupaten Ciamis. As for the analysis in this observation uses interview outcomes, documents study, observation outcomes and documentations that were obtained from relevant sources, using theory of Functions of Management by Harold Koontz and O’Donnell and elements of management. Observation outcomes show that fraud rates continue to increase without a balanced of settlement enhancement. Toward elements of management, related to efforts that have been done by Satreskim Polres Ciamis in order to handle criminal act of online fraud in Polres Ciamis jurisdiction, Satreskim Polres Ciamis lacks of qualified personnel, and lacks of budget support and adequate apparatus to carry out an investigation. Therefore in order to handle Satreskim requires a qualified and support of proper apparatus hardware and software and formation of cyber unit in Polres Ciamis. Keywords : law enforcement, cybercrime, cyberfraud, online fraud, effort, Satreskim.